2015
DOI: 10.3390/en81011187
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Load Management Approaches in Smart Grids

Abstract: Abstract:With rapid smart grid technology development, the customer can actively participate in demand-side management (DSM) with the mutual information communication between the distributor operation company and the smart devices in real-time. Controllable load management not only has the advantage of peak shaving, load balance, frequency regulation, and voltage stability, but is also effective at providing fast balancing services to the renewable energy grid in the distributed power system. The load manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 71 publications
0
34
0
2
Order By: Relevance
“…Moreover, the improvement of the quality of service is one of their main priorities [5,6]. Thus, an essential characteristic of a SG network is its strong Distributed Generation (DG) [7] and Distributed Energy Storage (DES) [8] presence, which together with Demand-Side Management (DSM) [9,10] systems make up microgrids [11] and provide improvements in the network reliability [12]. However, this presence shifts the traditional philosophy of Transmission and Distribution (T&D) systems, adding bidirectional energy flows along them.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the improvement of the quality of service is one of their main priorities [5,6]. Thus, an essential characteristic of a SG network is its strong Distributed Generation (DG) [7] and Distributed Energy Storage (DES) [8] presence, which together with Demand-Side Management (DSM) [9,10] systems make up microgrids [11] and provide improvements in the network reliability [12]. However, this presence shifts the traditional philosophy of Transmission and Distribution (T&D) systems, adding bidirectional energy flows along them.…”
Section: Introductionmentioning
confidence: 99%
“…The model demonstrated that moving from a day and night ET structure to a flat ET structure for a dairy farm resulted in significant electricity cost increases. Impacts of electricity pricing structures on REµGs have also been studied in [5][6][7][8][9][10][11][12][13][14][15][16][17] and it has generally been found that exposing electricity consumers to variable ET structures encourages demand response and promotes demand side management. FIT policies have proven successful in the growth of renewable energy implementations [8,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Harnessing demand-side flexibility through DR (some examples of which are given in [7,8,[10][11][12][13] within the broader concept of demand-side Table 1. Objectives for deploying demand-side flexibility.…”
Section: Introductionmentioning
confidence: 99%